The Politics of Emotions in ELT: Structure of Feeling and Anxiety of Korean English Teachers. Issue 3 (3rd July 2019) - Song, Juyoung; Park, Joseph Sung-Yul
ABSTRACT: Using the notion of structure of feeling by Raymond Williams, this article seeks to illuminate an ideological understanding of Korean English teachers' anxiety and deep sense of insecurity in English language teaching (ELT). Through a discussion of how their anxiety is grounded deeply within unequal social relations and how they reframe their anxiety through critical reflection on the cultural and ideological bias of their own anxiety, it points out the intricate relationship between ideology and emotion; teachers' emotions are shaped by dominant ideologies that constitute the social structures constraining their position as teachers, while their engagement with those emotions also enables their self-transformation towards gaining confidence as teachers. The results of the study emphasise the tension between social structure and agency in teachers' emotional experiences and discuss implications for teacher education and development.